Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

5 + 2(3 + 2x) = x + 3(x + 1)

Sagot :

Answer:

no solution

Step-by-step explanation:

5 + 2(3 + 2x) = x + 3(x + 1) ← distribute parenthesis on both sides

5 + 6 + 4x = x + 3x + 3 , simplify both sides

11 + 4x = 4x + 3 ( subtract 11 from both sides )

4x = 4x - 8 ( subtract 4x from both sides )

0 = - 8 ←  false statement

This indicates the equation has no solution